Neutrophil–lymphocyte ratio as a predictor of dengue hemorrhagic fever severity in Indonesian pediatric patients: A Single-center retrospective study - Dewi, I Gusti Ayu Ajeng Widia Kencana; Adiwinoto, Ronald Pratama; Rokhmadhoni Pikir, Rizqi; Rusli, Christina; Biutifasari, Verna; Diah Utami, Prawesty (PT. Mega Science Indonesia, 2025)
Dengue hemorrhagic fever (DHF) is a significant health burden in Indonesia, necessitating reliable prognostic markers for early clinical intervention. The neutrophil‒lymphocyte ratio (NLR) has emerged as a potential biomarker for disease severity assessment, although its utility in pediatric populations requires further validation. This study aimed to to determine the relationship between the neutrophil‒lymphocyte ratio and DHF severity grade in pediatric patients and evaluate its potential as a prognostic indicator for clinical decision-making. This retrospective cross-sectional study analyzed 111 pediatric patients aged 5-14 years who were diagnosed with DHF at RSPAL Dr. Ramelan, Surabaya, between January 2022 and December 2024. Patients were classified according to the WHO severity grades (I-IV), with the NLR calculated from complete blood counts obtained during days 3-6 of illness. Statistical analysis with Spearman's rank correlation was used to examine the relationship between the NLR and disease severity. The study population predominantly demonstrated Grade I DHF (56.8%), followed by Grade II DHF (20.7%), Grade III DHF (18.0%), and Grade IV DHF (4.5%). Patients with lower severity grades (I-II) predominantly presented low NLR values (<1) in 46.0% and 47.8% of cases, respectively, whereas those with higher severity grades (III-IV) primarily presented normal NLR values (1-3) in 65.0% and 60.0% of cases, respectively. Spearman's correlation analysis revealed no statistically significant relationship between the NLR and DHF severity (ρ = 0.120, p = 0.208). The neutrophil‒lymphocyte ratio has limited utility as a standalone predictor of DHF severity in pediatric patients. These findings suggest the need for alternative biomarkers or composite indices for accurate prediction of pediatric DHF severity.